2021
DOI: 10.1111/ijlh.13681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Scopio Labs X100 Full Field PBS: The first high‐resolution full field viewing of peripheral blood specimens combined with artificial intelligence‐based morphological analysis

Abstract: Background Current digital cell imaging systems perform peripheral blood smear (PBS) analysis in limited regions of the PBS and require the support of manual microscopy without achieving full digital microscopy. We report a multicenter study that validated the Scopio Labs X100 Full Field PBS, a novel digital imaging system that utilizes a full field view approach for cell recognition and classification, in a decision support system mode. Methods We analyzed 335 normal and 310 abnormal PBS from patients with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…Last, although we evaluated within-laboratory precision, we could not evaluate interlaboratory precision. Evaluation of interlaboratory precision is important to ensure reliable and comparable results between DM analyzers performed at different laboratories [ 33 , 36 ]. A standardized approach and protocol are also necessary for evaluating precision of WBC differentials in both DM analyzers and manual count [ 4 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Last, although we evaluated within-laboratory precision, we could not evaluate interlaboratory precision. Evaluation of interlaboratory precision is important to ensure reliable and comparable results between DM analyzers performed at different laboratories [ 33 , 36 ]. A standardized approach and protocol are also necessary for evaluating precision of WBC differentials in both DM analyzers and manual count [ 4 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent study reported on the use of a novel AI-based decision support system that utilised a full-field approach for blood cell recognition and classification in both normal and abnormal peripheral blood films. 8 Impressive degrees of correlation with conventional manual microscopy were achieved. Such systems will not replace morphologists but act as a labourassistance device to alleviate busy workloads.…”
Section: W I D E R P E R S P E C T I V E Smentioning
confidence: 99%
“…It has been estimated that some 15% of blood samples require manual review 7 . A recent study reported on the use of a novel AI‐based decision support system that utilised a full‐field approach for blood cell recognition and classification in both normal and abnormal peripheral blood films 8 . Impressive degrees of correlation with conventional manual microscopy were achieved.…”
Section: Educational Content Learning and Assessment Commentsmentioning
confidence: 99%
“…In October of 2020, the U.S. Food and Drugs Administration (FDA) cleared Scopio Labs' X100 Full-Field PBS system. A digital PBS morphological analyzer with full field specimen view, which offers fully digital and remote option for PBSs evaluation, interpretation and review 6 . As previously reported by Katz et al 6 , the Scopio Labs X100 Full-Field PBS system has demonstrated that, under clinical study settings where each examiner reported a 200white blood cell (WBC) differential, complete red blood cell (RBC) morphology evaluation and platelet estimation, the median time for PBS review was 7:46 minutes, a 60% improvement of workflow efficiency, when compared to a manual PBS review of 20.0 minutes per case 6 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…PBS examination by manual microscopy remains one of the most time consuming and laborintensive procedures in the laboratory, requiring specialized staff, which negatively impacts TAT, particularly during weekends with limited staff availability 2,3 . The increased demand for hematological morphology tests such as the PBS with clearly defined TATs, the complexity of PBS analysis, and the speed of diagnosis to enable immediate clinical action, coupled with the shortage of skilled morphologists and increasing pressure for cost containment, is driving digitalization of microscopy and remote review to the forefront of laboratory workflow management 2,4,6,7,8 .…”
mentioning
confidence: 99%